2017
DOI: 10.1155/2017/4810672
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of Thiazolidinediones and PPARγin Bladder Cancer

Abstract: The use of thiazolidinedione (TZD) therapy in type II diabetic patients has proven useful in the lowering of blood glucose levels. However, recent investigations have shown that there may be potential health concerns associated, including the risk of developing bladder cancer as well as complications in the cardiovasculature. TZDs are ligands for the nuclear receptor PPARγ, and activation causes lipid uptake and insulin sensitization, both of which are critical processes for diabetic patients whose bodies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
(119 reference statements)
1
19
1
Order By: Relevance
“…[33][34][35] Some synthetic PPARc ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis. [36][37][38][39][40] In this study, we found that TNBG-5602 can increase the expression of PPARc at the mRNA and protein levels in vitro and in vivo. Further study found that a PPARc agonist (RSG) can enhance the lipid accumulation of TNBG-5602, while a PPARc inhibitor (T0070907) can reverse the lipid accumulation of TNBG-5602.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[33][34][35] Some synthetic PPARc ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis. [36][37][38][39][40] In this study, we found that TNBG-5602 can increase the expression of PPARc at the mRNA and protein levels in vitro and in vivo. Further study found that a PPARc agonist (RSG) can enhance the lipid accumulation of TNBG-5602, while a PPARc inhibitor (T0070907) can reverse the lipid accumulation of TNBG-5602.…”
Section: Discussionmentioning
confidence: 52%
“…It was discovered that overexpression of PPARγ can inhibit cell proliferation and tumour growth, while it is reversed in PPARγ‐silenced cancer cells . Some synthetic PPARγ ligands, such as rosiglitazone, troglitazone and ciglitazone, inhibit the proliferation of tumour cells and induce tumour cell apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…With stronger metabolic activity than that of the natural ligand, the synthetic ligand is widely used in diabetes management. Moreover, a growing body of research has discovered that the synthetic ligand has an antitumor effect either used independently or combined with other medications, and the mechanism underlying this is a research hotspot at present [ 13 ]. Certain nonsteroidal drugs, such as indomethacin and ibuprofen, are reported to possess an antineoplastic effect, although their metabolic activity is extremely low [ 14 ].…”
Section: Overview Of Ppar γmentioning
confidence: 99%
“…Currently, the U.S. Food and Drug Administration allows the use of pioglitazone in patients with special caution to those with a prior history or active BC [10]. A potential reason for this observation could be that PPARγ signaling in BC cells may provide a tumor micro-environment that allows for de novo lipogenesis of lipids that can be utilized in increasing tumor mass and energy usage [11]. However, other studies have shown that TZDs posed no risk on survival in BC patients who underwent radical cystectomy [12].…”
Section: Introductionmentioning
confidence: 99%